Free Press under Threat in Hong Kong Protest Fallout - Chris Yeung (Contemporary Chinese Political Economy and Strategic Relations: An International Journal, 2020)
A government bill on cross-border transfer of fugitives whipped up a storm of protests in Hong Kong in June 2019. It soon morphed into a social movement against police brutality, authoritarian rule and resistance against the “one country, two systems” constitutional framework. To suppress dissent, the Chinese Central Government and the Hong Kong SAR government have tightened social and political control and undermined checks and balances in the society. Independent and free media is under increasing threat.